Respuesta :
Answer:
x is 2
Step-by-step explanation:
[tex]3x(12x - 4) - 9x(4x - 3) = 30[/tex]
• First open brackets [ by distributive property ]
[tex]( {36x}^{2} - 12x) - ( {36x}^{2} - 27x) = 30 \\ \\ - 12x + 27x = 30 \\ \\ 15x = 30 \\ \\ x = 2[/tex]
Answer:
[tex]x=2[/tex]
Step-by-step explanation:
[tex]3x\left(12x-4\right)-9x\left(4x-3\right)=30[/tex]
Expand: [tex]3x\left(12x-4\right)[/tex]
Apply distributive law:
[tex]36x^2-12x[/tex]
---------
Expand: [tex]-9x(4x-3)[/tex]
Apply distributive law:
[tex]36x^2+27x[/tex]
---------
[tex]36x^2-12x-36x^2+27x[/tex]
Combine like terms:
[tex]36x^2-36x^2-12x+27x[/tex]
[tex]-12x+27x[/tex]
[tex]15x[/tex]
[tex]15x=30[/tex]
Divide both sides by 15:
[tex]\frac{15x}{15}=\frac{30}{15}[/tex]
[tex]x=2[/tex]
OAmalOHopeO